The Influence of Financial Literacy, Digital Literacy and Risk and Return Perceptions on the Investment Interest of MSMEs in Surabaya City - Farah Huda Aisyah; Risky Budianto (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyze the influence of financial literacy, digital literacy, and risk and return perception on the investment interest of MSME actors in Surabaya City. MSMEs have a strategic role in the regional economy but still face challenges in financial management and investment decision-making. This study employed a quantitative approach with an explanatory research design. Data were collected through questionnaires distributed to MSME actors in Surabaya City using purposive sampling techniques, resulting in 170 respondents. Data analysis was conducted using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method. The results indicate that financial literacy, digital literacy, and risk and return perception have a positive effect on the investment interest of MSME actors in Surabaya City. These findings suggest that financial understanding, the utilization of digital technology, and positive perceptions of investment risk and return play an important role in increasing investment interest among MSME actors. The study implies the importance of improving digital capabilities and investment understanding to support long-term financial management and business sustainability among MSMEs.